Impact of intestinal bacteria on biofilm formation, motility, virulence, and gene expression in Vibrio parahaemolyticus - Qinglian Huang; Xin Shen; Xi Luo; Miaomiao Zhang; Xue Li; Shenjie Ji; Yiquan Zhang; Renfei Lu (Microbiology Spectrum)
ABSTRACT Vibrio parahaemolyticus, a foodborne pathogen, is a leading cause of acute gastroenteritis in humans. In contrast, non-pathogenic Escherichia coli is a common commensal bacterium residing in the human gut. Despite their co-occurrence during infection, the interaction between these two species remains poorly understood. This study revealed that V. parahaemolyticus outcompetes E. coli under co-culture conditions, demonstrating superior growth efficiency and competitive dominance. Co-cultivation stimulated biofilm formation in both species, with E. coli culture supernatant specifically enhancing biofilm development in V. parahaemolyticus. Nevertheless, V. parahaemolyticus dominated mixed microbial colonies. Additionally, co-cultivation reduced V. parahaemolyticus cell adhesion and swimming motility but heightened its cytotoxicity. RNA-seq analysis identified 629 differentially expressed genes in co-cultured V. parahaemolyticus compared to monocultured cells, including 290 upregulated and 339 downregulated genes. Genes related to flagella and type III secretion system 1 were downregulated, while those for exopolysaccharides, type IV pili, and type VI secretion system 2 were upregulated. Notably, eight genes involved in c-di-GMP metabolism showed significant changes, with seven being upregulated. Additionally, 22 putative transcriptional regulators exhibited differential expression, indicating tightly coordinated gene expression during interspecies interactions. These findings illuminate the dynamic interplay between V. parahaemolyticus and gut commensals, providing insights into pathogen behavior in polymicrobial environments. This work lays the groundwork for future studies on gut microbiota-pathogen interactions and their implications for infectious disease mechanisms.IMPORTANCEThis study reveals critical insights into the interplay between the gut commensal bacterium E. coli and the foodborne pathogen V. parahaemolyticus, offering novel perspectives on how gut microbiota influence pathogen behavior. V. parahaemolyticus outcompetes E. coli in co-culture, highlighting its adaptability and potential to disrupt gut microbial balance during infection. The E. coli culture supernatant enhances V. parahaemolyticus biofilm formation. Co-cultivation reduces V. parahaemolyticus motility but increases cytotoxicity. RNA-seq analysis identified 629 differentially expressed genes, including those associated with downregulated flagellar/T3SS1 systems and upregulated exopolysaccharide/T6SS2 pathways. These findings advance our understanding of gut microbiota-pathogen dynamics and could inform strategies to mitigate V. parahaemolyticus infections by targeting interspecies signaling or virulence pathways.